DARI LAWET KEBUMEN KE PANCEN MAEN: MENGATASI PERMASALAHAN ADOPSI LAYANAN KEPENDUDUKAN DIGITAL DI KEBUMEN - Erowati, Dewi; Astuti, Pudji (Universitas Jenderal Ahmad Yani, 2025)
Adoption of digital civil registration services in Kebumen Regency through Lawet Kebumen and Pancen Maen applications is still low, although these technologies are designed to improve the efficiency of civil registration administration. This study used descriptive qualitative and quantitative methods, with surveys, interviews, and secondary data analysis from Disdukcapil Kebumen. The data showed that out of 1,271,875 residents, only 5.69% had activated the Digital Population Identity (IKD), reflecting the low acceptance of the technology. Based on the Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), and Diffusion of Innovations (DOI) theories, the main barriers include perceived usefulness and ease of use, social norms that support conventional methods, and limited access to technology in peripheral areas. Concerns over personal data security are also a significant factor slowing down adoption. This research recommends socialization of digital literacy, equitable infrastructure development, strengthening data security, and community approaches to change social norms. These strategies are expected to increase the adoption of digital services in Kebumen, thereby accelerating a more inclusive and efficient civil registration modernization.